Pengaruh Disiplin dan Iklim Kerja terhadap Kinerja Kepala Sekolah pada Sekolah Menengah Kejuruan Muhammadiyah Cipulir, Jakarta Selatan - Hendrian Yonata; Hadion Wijoyo; Denok Sunarsi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
This study aims to determine the effect of discipline and work climate on the performance of school principals at Cipulir Muhammadiyah Vocational High School, South Jakarta. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study, the discipline has a significant effect on the performance of the principal by 51.9%, the hypothesis test is obtained t count> t table or (7.568> 2.006). Work climate has a significant effect on the performance of school principals by 44.0%, hypothesis testing is obtained t count> t table or (6.456> 2.006). Discipline and work climate simultaneously have a significant effect on the performance of school principals with the regression equation Y = 7.924 + 0.419X1 + 0.387X2 and the influence contribution is 61.6%, the hypothesis test obtained F count> F table or (41.741> 2.780).